1999
DOI: 10.1101/gad.13.19.2527
|View full text |Cite
|
Sign up to set email alerts
|

Conserved requirement for EGF-CFC genes in vertebrate left-right axis formation

Abstract: Specification of the left-right (L-R) axis in the vertebrate embryo requires transfer of positional informationfrom the node to the periphery, resulting in asymmetric gene expression in the lateral plate mesoderm. We show that this activation of L-R lateral asymmetry requires the evolutionarily conserved activity of members of the EGF-CFC family of extracellular factors. Targeted disruption of murine Cryptic results in L-R laterality defects including randomization of abdominal situs, hyposplenia, and pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
219
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(234 citation statements)
references
References 54 publications
12
219
2
1
Order By: Relevance
“…Because several studies have suggested that absent gene expression correlates with the incidence of isomerisms (Yan et al, 1999; Meno et al, 1998; Ibanes and Izpisua Belmonte, 2009), and because both absent gene expression and isomerisms are common in the mouse model (Figure 4 and data not shown), I also addressed whether there was a direct relationship between the incidence of absent nodal expression and the frequency of isomerisms. When all animals with these two measures were included in this regression analysis, there was no statistically significant relationship observed (R 2 =0.004, p=0.750).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because several studies have suggested that absent gene expression correlates with the incidence of isomerisms (Yan et al, 1999; Meno et al, 1998; Ibanes and Izpisua Belmonte, 2009), and because both absent gene expression and isomerisms are common in the mouse model (Figure 4 and data not shown), I also addressed whether there was a direct relationship between the incidence of absent nodal expression and the frequency of isomerisms. When all animals with these two measures were included in this regression analysis, there was no statistically significant relationship observed (R 2 =0.004, p=0.750).…”
Section: Resultsmentioning
confidence: 99%
“…A considerable number of studies have reported complete absence of nodal, lefty, or pitx2 expression (Field et al, 2011; Oki et al, 2010; Sakano et al, 2010; Gaio et al, 1999; Takeuchi et al, 2007; Zhang et al, 2001; Yan et al, 1999; Tsukui et al, 1999; Collignon et al, 1996; Kramer-Zucker et al, 2005; Krebs et al, 2003; Pennekamp et al, 2002), with some reporting 100% absent expression for all three genes. What does complete absence of gene expression mean?…”
Section: Discussionmentioning
confidence: 99%
“…Although significant attention has been paid to zebrafish mutations that randomize L-R asymmetry (e.g. Chen et al, 1997;Yan et al, 1999;Bisgrove et al, 2000;Chin et al, 2000), little is known regarding the molecular mechanisms that translate L-R patterning into directed cardiac morphogenesis. Future studies of mutations that interfere with cardiac looping without disrupting initial L-R patterning will be particularly informative in this regard.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…Rotation of the heart cone during jogging might be directing the later torsion of the heart tube leading to D-loop in normal conditions. However, this seems unnecessary as mutants with no jog retain their ability to loop [62,63,[68][69][70]. Indeed, the heart tube in the absence of Nodal signalling shows D-loop in about 70% of embryos and this is maintained even after the heart tube is cultured ex vivo [67].…”
Section: Coexistence Of Different Types Of Asymmetries: Epithalamus Amentioning
confidence: 99%